2D Electrical Imaging Surveys for Leachate Plume Migration at an Old Dump Site in Ibadan South Western Nigeria: A Case Study. (26th March 2014) - Omolayo, Dare; Tope, Fatoba Julius
Abstract : The site surveyed is along a popular ring road in Ibadan. It is an old dump site which had been closed over a long period of time. Development into industrial and residential house schemes had crowded around the site. This development resulted in the exploitation of groundwater within the thick regolith that characterize the area. The investigation was carried out to ascertain leachate plume generation and migration and its impact on the surrounding soil and the groundwater. 2D electrical resistivity imaging using Wenner array was used to delineate the plume and probable trend of migration. The method involves the injection of low frequency DC current into the subsurface and measuring the potential difference set up by another pair of electrodes called potential electrodes. All the traverses show areas of very low resistivity values ranging between 4 ohm-m and 13.8 ohm-m; in addition to this, the water samples collected from hand dug wells that surround the dump site show high total dissolved solids (TDS) with an average value of 2033 mg/L, high conductivity with an average value of 2868 mg/L, and high nitrate value (63 mg/L); these values are above the World Health Organization (WHO) permissible values. This poses a health challenge to the residents living around this site.